Multimaterial bioprinting—minus the printer: Synthetic bacterial patterning with UV-responsive genetic circuits. (June 2021) - Gumuskaya, Gizem
In this paper, we argue that synthetic biology can help us employ living systems' unique capacity for self-construction and biomaterial production toward developing novel architectural fabrication paradigms, in which both the raw material production and its refinement into a target structure can be merged into a single computational process embedded in the living structure itself. To demonstrate, here we introduce bioPheme, a novel biofabrication method for engineering bacteria to build biomaterial(s) of designer's choice into arbitrary 2D geometries specified via transient UV tracing. To this end, we present the design, construction, and testing of the enabling synthetic DNA circuit, which, once inserted into a bacterial colony, allows the bacteria to execute spatial computation by interacting with one another based on the if-then rules encoded in this circuit. At the heart of this genetic circuit is a pair of UV sensor – actuator, and a pair of cell-to-cell signal transmitter – receptor modules, created with genes extracted from the virus λ Phage and marine bacterium Vibrio fischeri, respectively. These modules are wired together to help designers engineer bacteria to build macro-scale structures with seamlessly integrated biomaterials, thereby bridge the molecular and architectural scales. In this way, a bacterial lawn can be programmed to produce different objects with complementary biomaterial compositions, such as a biomineralized superstructure and an elastic tissue filling in-between. In summary, this paper focuses on how scientists' increasing ability to harness the innate computational capacity of living cells can help designers create self-constructing structures for architectural biofabrication. Through the discussions in this paper, we aim to initiate a shift in today's biodesign practices toward a greater appreciation and adoption of bottom-up governance of living structures. We are confident that such a paradigm shift will allow for more efficient and sustainable biofabrication systems in the 4th industrial revolution and beyond.